1998
DOI: 10.1103/physrevlett.80.1662
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Critical Fluctuations after Cessation of Simple Shear Flow

Abstract: Scattering experiments under shear of a near-critical system show a highly anisotropic static structure factor. We present small angle light scattering experiments on the relaxation of this anisotropic structure factor of a near-critical colloidal system after cessation of a simple shear flow. The structure factor is found to develop a scattering ring, which shifts to smaller wave vectors in time and increases in intensity. A theoretical explanation of this phenomenon is proposed. [S0031-9007(98)05367-8] PACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The phase-ordering dynamics of such systems have just begun to be investigated, and the underlying physics may have relevance to such things as the crystallization of globular proteins and nematic ordering of rodlike particles in the presence of a nonadsorbing polymer [6,7]. Beyond their broad commercial significance, colloidal suspensions serve as useful models for a variety of condensed matter systems, from crystals [8,9] and glasses [10] to critical fluids [11] and fractal networks [12]. In this Letter, video microscopy is used to study depletion driven selfassembly in confined binary suspensions of nearly hardsphere colloids.…”
mentioning
confidence: 99%
“…The phase-ordering dynamics of such systems have just begun to be investigated, and the underlying physics may have relevance to such things as the crystallization of globular proteins and nematic ordering of rodlike particles in the presence of a nonadsorbing polymer [6,7]. Beyond their broad commercial significance, colloidal suspensions serve as useful models for a variety of condensed matter systems, from crystals [8,9] and glasses [10] to critical fluids [11] and fractal networks [12]. In this Letter, video microscopy is used to study depletion driven selfassembly in confined binary suspensions of nearly hardsphere colloids.…”
mentioning
confidence: 99%
“…The first relaxation contribution is large at large K, while the second contribution is large at small K. This leads to a maximum of the relaxation rate at finite wave vectors. This competition of two relaxation mechanisms is responsible for a maximum in scattering pattern after cessation of shear flow [31].…”
Section: E Structure Factor Under Oscillatory Shear Flowmentioning
confidence: 99%
“…In the present paper we investigate, both theoretically and experimentally, the response of a near-critical colloid-polymer mixture to stationary and oscillatory shear flow. Thus we pursue the line set by earlier scattering experiments on critical dispersions of attractive colloids [29][30][31][32][33] under shear. Having established the link between the experimentally determined and theoretically calculated microstructure, one can continue to predict rheological behavior [18], since it has been shown that shearinduced distortions of the critical structure factor of such dispersions are the origin of near-critical viscoelastic behavior [30].…”
Section: Introductionmentioning
confidence: 99%